Did the Federal Trade Commission's Advertising Substantiation Program Promote More Credible Advertising? - Sauer, Raymond D.; Leffler, Keith B. (American Economic Review, 1990)
This paper examines the effects of the Federal Trade Commission's Advertising Substantiation Program, developed in the early 1970s. This program coupled changes in the legal definition of deception with more vigorous FTC enforcement. The authors analyze changes in advertising intensity, media choice, media wealth, and the progress of new entrants. The evidence suggests that adoption of substantiation requirements increased the credibility of advertising. Copyright 1990 by American Economic Association.